2003
DOI: 10.1007/s00484-003-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of predictive forecasting of Juniperus ashei pollen movement in the Southern Great Plains, USA

Abstract: Juniperus ashei pollen, a significant aeroallergen, has been recorded during December and January in Tulsa, Oklahoma, over the past 20 years. The nearest upwind source for this pollen is populations growing in southern Oklahoma and central Texas, at distances of 200 km and 600 km respectively. Long-distance dispersal of J. ashei pollen into the Tulsa area shows a strong correlation with the trajectories of wind blowing across southern populations before traveling north towards eastern Oklahoma. The strong tie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 16 publications
0
27
0
3
Order By: Relevance
“…Nevertheless, pollen from taxa not representative of the local or regional vegetation is also recorded, implying long-range transport (Munuera Giner et al 2002;). The distance pollen travels, once released into the air, is closely related to the wind as a vectorial quantity (Solomon 1984;Hjelmroos 1991;Cour et al 1999;Munuera Giner et al 1999;Van de Water et al 2003). Long-distance pollen transport into the city of Thessaloniki has been confirmed by aerobiological records .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, pollen from taxa not representative of the local or regional vegetation is also recorded, implying long-range transport (Munuera Giner et al 2002;). The distance pollen travels, once released into the air, is closely related to the wind as a vectorial quantity (Solomon 1984;Hjelmroos 1991;Cour et al 1999;Munuera Giner et al 1999;Van de Water et al 2003). Long-distance pollen transport into the city of Thessaloniki has been confirmed by aerobiological records .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis of the effect of wind is necessary if we are to achieve forecasting ability regarding the air pollen load. Pollen can be transferred from distant sources outside the sampling area (Stix 1975;Solomon and Mathews 1978;Hjelmroos 1991;Campbell et al 1999;Cour et al 1999;Van de Water et al 2003). This is particularly true in urban areas, where Burkard traps are usually located.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…At an ecological level, such conversion exacerbates landscape fragmentation (Coppedge et al 2002), eliminates habitat for grassland species (Coppedge et al 2001;Rosenstock and Van Riper 2001;Horncastle et al 2005;Frost and Powell 2011), reduces plant species richness (Ratajczak et al 2012), and changes carbon cycling and storage Natural Areas Journal 119 (Wessman et al 2004;Barger et al 2011). Societal effects of grassland conversion include lost forage, lost or fragmented ranches and the economic (livestock production) and recreational (hunting, birding, aesthetic) benefits they provide, as well as increased wildfire danger resulting from increased fuel loading (Burkinshaw and Bork 2009) and human health issues exacerbated by allergenic juniper pollen pulses (Van de Water et al 2003). Once converted, restoring shrub/tree-invaded areas back to functioning grassland can be costly (Ortmann et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Airborne pollen is very mobile, due to its size and structure. The long-distance transport of pollen is well known, and several studies have demonstrated the ability of airborne pollen to transfer hundreds of kilometres away (Cambon et al, 1992;Cabezudo et al, 1997;Latorre, 1997;Jato et al, 2002b;Kasprzyk, 2003;Rousseau et al, 2003;Van de Water et al, 2003;Lorenzo et al, 2006;Ranta et al, 2006;Estrella et al, 2006). Therefore, pollen found in airborne pollen traps does not necessarily reflect the pollen from the studied surroundings.…”
Section: Introductionmentioning
confidence: 99%